Crucial role of ocean-atmosphere coupling on the Indian monsoon anomalous response during dipole events - Krishnan, R.; Sundaram, Suchithra; Swapna, P.; Kumar, Vinay; Ayantika, D. C.; Mujumdar, M. (Climate Dynamics, 2011)
This paper examines an issue concerning the simulation of anomalously wet Indian summer monsoons like 1994 which co-occurred with strong positive Indian Ocean Dipole (IOD) conditions in the tropical Indian Ocean. Contrary to observations it has been noticed that standalone atmospheric general circulation models (AGCM) forced with observed SST boundary condition, consistently depicted a decrease of the summer monsoon rainfall during 1994 over the Indian region. Given the ocean-atmosphere coupling during IOD events, we have examined whether the failure of standalone AGCM simulations in capturing wet Indian monsoons like 1994 can be remedied by including a simple form of coupling that allows the monsoon circulation to dynamically interact with the IOD anomalies. With this view, we have performed a suite of simulations by coupling an AGCM to a slab-ocean model with spatially varying mixed-layer-depth (MLD) specified from observations for the 1994 IOD; as well as four other cases (1983, 1997, 2006, 2007). The specification of spatially varying MLD from observations allows us to constrain the model to observed IOD conditions. It is seen that the inclusion of coupling significantly improves the large-scale circulation response by strengthening the monsoon cross-equatorial flow; leading to precipitation enhancement over the subcontinent and rainfall decrease over south-eastern tropical Indian Ocean-in a manner broadly consistent with observations. A plausible physical mechanism is suggested to explain the monsoonal response in the coupled frame-work. These results warrant the need for improved monsoon simulations with fully coupled models to be able to better capture the observed monsoon interannual variability.
Keywords: Anomalous wet Indian monsoons; Indian ocean dipole; Numerical simulation; Ocean-atmosphere coupling

Long-lived monsoon depressions of 2006 and their linkage with the Indian ocean Dipole - Krishnan, R.; Ayantika, D. C.; Kumar, Vinay; Pokhrel, Samir (International Journal of Climatology, 2011)
A highlight of the 2006 boreal summer monsoon season was the enhanced activity of long-lived monsoon depressions and low-pressure systems (LPS) over the Indian region. Another important phenomenon during this period was the evolution of a positive Indian Ocean Dipole (PIOD) event. Although previous studies have investigated the impact of PIOD on the large-scale monsoon response, their influence on monsoon LPS activity is not well understood. Based on detailed diagnostic analyses of monsoon LPS during 2006, as well as those associated with other PIOD events during 1958-2007, the present work addresses two specific issues concerning the roles of (a) PIOD-induced large-scale circulation changes and (b) internal feedbacks between latent heating and dynamics, in sustaining the monsoon LPS activity. The results show that PIOD conditions generally favour increased propensity of long-lived (>5 days) LPS with long westward tracks extending into northwest India. The average contribution of long-lived monsoon LPS to the total is found to be approximately 12% higher during PIOD episodes as compared to non-PIOD. The PIOD events showed two important large-scale elements conducive for enhancement of LPS activity: (a) strengthening of cross-equatorial moisture transport from south-eastern tropical Indian Ocean into the Bay of Bengal and (b) enrichment of barotropic instability of monsoon flow. Estimates of latent-heating profiles from TRMM-satellite products during the 2006 LPS showed heating in the mesoscale updrafts above 600 hPa with maximum approximately 400 hPa; while cooling prevailed in lower levels. Stratiform precipitation covered approximately 70-85% of rain area during the prolonged LPS; and the large-scale monsoon Hadley-type circulation was found to be intensified with strong mid-level inflows entering the stratiform rain region. The overall findings suggest that the PIOD-induced background circulation together with internal feedbacks between mesoscale convective systems and large-scale circulation can effectively enhance the longevity of monsoon LPS. These results should serve as important inputs for numerical weather forecasting of extreme rainfall events associated with the regional monsoon phenomenon. Copyright (C) 2010 Royal Meteorological Society
Keywords: Indian ocean dipole; life period; monsoon depressions